2021
DOI: 10.1093/neuros/nyaa553
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery for Atypical (World Health Organization II) and Anaplastic (World Health Organization III) Meningiomas: Results From a Multicenter, International Cohort Study

Abstract: BACKGROUND Atypical and anaplastic meningiomas have reduced progression-free/overall survival (PFS/OS) compared to benign meningiomas. Stereotactic radiosurgery (SRS) for atypical meningiomas (AMs) and anaplastic meningiomas (malignant meningiomas, MMs) has not been adequately described. OBJECTIVE To define clinical/radiographic outcomes for patients undergoing SRS for AM/MMs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 30 publications
(54 reference statements)
1
33
0
Order By: Relevance
“…We did not nd that higher radiation doses correlated with improved tumor control. This is nearly identical to the 5-year PFS after SRS for patients with AM in the multicenter study of Shepard et al (36%), [19] and after EBRT in Radiation Therapy Oncology Group (RTOG) 0589 study (40%).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…We did not nd that higher radiation doses correlated with improved tumor control. This is nearly identical to the 5-year PFS after SRS for patients with AM in the multicenter study of Shepard et al (36%), [19] and after EBRT in Radiation Therapy Oncology Group (RTOG) 0589 study (40%).…”
Section: Discussionsupporting
confidence: 74%
“…A number of studies advocate upfront adjuvant EBRT, [8][9][10] some reports favor post-operative surveillance with salvage radiotherapy especially for those following GTR, [11][12][13]18] while a third group advocate for SRS either as an adjuvant or salvage technique. [15,17,19,20] We found that upfront adjuvant SRS and salvage SRS for late recurrences were equally effective, whereas salvage SRS for early recurrence (7-18 months following resection) was a signi cant risk for tumor progression. One explanation may be that patients with earlier disease progression have more aggressive tumors, perhaps related to increased proliferation indices, which has been correlated with reduced e cacy after SRS of AM and MM.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations